Pengaruh Kemampuan Berpikir Positif dan Konsep Diri terhadap Prestasi Belajar Matematika Siswa - Muhamad Buhais; Bondan Dwi Hatmoko (SAP (Susunan Artikel Pendidikan), 2022)
The purpose of this study was to determine: (1) the effect of positive thinking skills and self-concept together on the mathematics learning achievement of private vocational high school students in Bekasi, (2) The effect of positive thinking skills on mathematics learning achievement of private vocational high school students in Bekasi, (3) the influence of self-concept on mathematics learning achievement of private SMK students in Bekasi. The research method used in this study is a quantitative survey method, and then the survey data are analyzed using multiple regression analysis.  In the description of the research data, the results of the research can be stated from the data obtained including the highest, lowest, average, (mean) mode, median scores. In processing the data obtained, the researchers carried out processing with the help of Microsoft Exel and SPSS 20 applications. The results of the study concluded that there was an insignificant effect of positive thinking ability and self-concept together on students' mathematics learning achievement.